2020
DOI: 10.1017/s0022149x20000723
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol potential ofSteinernema cholashanense(Nguyen) on larval and pupal stages of potato tuber moth,Phthorimaea operculella(Zeller)

Abstract: The potato tuber moth, Phthorimaea operculella (Zeller), is a serious pest of potato and other commercial crops belonging to the Solanaceae family. In recent years, it has become an emerging problem in potato-growing regions of the Nilgiri hills of southern India. It is responsible for the reduced quality and quantity of marketable potatoes. In this regard, the development of an eco-friendly control method for the management of the potato tuber moth is urgently required. Therefore, in the present study, the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…They determined that the fourth instar stage was the most susceptible. Mhatre et al (2020) reported that Steinernema cholashanense caused the greater mortality in the fourth-instar larval stage (100%) compared to the pupae (30%). Kepenekci et al (2013) investigated the efficacy of S. carpocapsae, S. feltiae and H. bacteriophora, which are detected in Turkey, against potato moth P. operculella.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They determined that the fourth instar stage was the most susceptible. Mhatre et al (2020) reported that Steinernema cholashanense caused the greater mortality in the fourth-instar larval stage (100%) compared to the pupae (30%). Kepenekci et al (2013) investigated the efficacy of S. carpocapsae, S. feltiae and H. bacteriophora, which are detected in Turkey, against potato moth P. operculella.…”
Section: Resultsmentioning
confidence: 99%
“…EPNs can serve as an effective supplementary control as part of an integrated pest management (IPM) strategy (Odendaal et al, 2015;Belien, 2018;Gulcu et al, 2017). A few studies have investigated the effects of EPNs against potato tuber moth ( Kepenekci et al, 2013;Mhatre et al, 2020;Yan et al, 2020;Orakçı, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have determined the activities of EPNs on P. operculella (Ivanova et al, 1994;Sweelam et al, 2010;Hassani-Kakhki et al, 2013;Abdelmonem et al, 2018;Moawad et al, 2018;Mhatre et al, 2020;Yan et al, 2020;Ebrahimi et al, 2021). Some studies also use EPNs to supplement chemical applications against P. operculella (Kary et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of the genus Steinernema reported in India is apparently very high ( Bhat et al, 2020a ), with 14 species isolated from Indian soils ( Bhat et al, 2021a ) from more than 125 valid Steinernema species. The Steinernema species that have been isolated from the Indian subcontinent include four from the “ Bicornutum ” clade: S. bicornutum ( Hussaini et al, 2001 ), S. riobrave ( Ganguly et al, 2002 ), S. pakistanense ( Bhat et al, 2018 ), and S. abbasi ( Bhat et al, 2021a ); four from the “ Carpocapsae ” clade: S. carpocapsae ( Hussaini et al, 2001 ), S. tami ( Hussaini et al, 2001 ), S. surkhetense ( Bhat et al, 2017 ), and S. siamkayai ( Bhat et al, 2021b ); three from the “ Glaseri ” clade: S. sangi ( Yadav et al, 2012 ), S. indicum ( Patil et al, 2023 ) and S. hermaphroditum ( Bhat et al, 2019 ); and three from the “ Glaseri ” clade: S. sangi ( Lalramnghaki et al, 2017 ), S. cholashanense ( Mhatre et al, 2017 ), and S. feltiae ( Askary et al, 2020 ). In addition, three species, S. thermophilum , S. meghalayense , and S. dharanai , were synonymized with already existing species: S. abbasi, S. carpocapsae , and S. hermaphroditum , respectively ( Ganguly & Singh, 2000 ; Ganguly et al, 2011 ; Kulkarni et al, 2012 ; Hunt & Subbotin, 2016 ).…”
mentioning
confidence: 99%